2017
DOI: 10.1111/pace.13046
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between QRS and T Waves Using a Right Parasternal Lead for S‐ICD in a Patient with a Single Ventricle

Abstract: The subcutaneous implantable cardioverter-defibrillator (S-ICD) is a useful option for patients with a single ventricle (SV) in which transvenous leads are contraindicated because of intracardiac shunts. We report a case in which a right parasternal lead placement was indicated for an S-ICD in a resuscitated patient with an SV. There were significant changes in the magnitude of R to T waves ratio in the right compared to the left parasternal lead position. Screening in the right parasternal position is effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Previous work has shown that Sn can be a beneficial additive to metal catalysts for a range of chemical reactions. [14][15][16][17][18][19][20] Electronic effects have been observed in metal-Sn alloys resulting in a decreased heat of adsorption for CO. 21 These reported electronic effects may help decrease the rate of deactivation due to self-poisoning. 22 Furthermore, Chiappero et al have demonstrated that Pt alloyed with Sn can improve the selectivity to alpha olefins formed during the deoxygenation of methyl esters under semi-batch conditions at temperatures ranging from 593 K to 623 K and pressures ranging from 0.2 MPa to 1.14 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that Sn can be a beneficial additive to metal catalysts for a range of chemical reactions. [14][15][16][17][18][19][20] Electronic effects have been observed in metal-Sn alloys resulting in a decreased heat of adsorption for CO. 21 These reported electronic effects may help decrease the rate of deactivation due to self-poisoning. 22 Furthermore, Chiappero et al have demonstrated that Pt alloyed with Sn can improve the selectivity to alpha olefins formed during the deoxygenation of methyl esters under semi-batch conditions at temperatures ranging from 593 K to 623 K and pressures ranging from 0.2 MPa to 1.14 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant atrial or ventricular arrhythmia during the observation. ECG changes are not specific for PAH, however, several studies show a predictive value of ECG in adult PAH patients [6,7,8,9,10,11,12]. Igata et al [6] demonstrate that the amplitude of RV1+SV5/6 inversely correlates with mean pulmonary artery pressure (mPAP) and right ventricular ejection fraction and patients with an amplitude greater than 16.4 mm had a worse prognosis during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Igata et al [6] demonstrate that the amplitude of RV1+SV5/6 inversely correlates with mean pulmonary artery pressure (mPAP) and right ventricular ejection fraction and patients with an amplitude greater than 16.4 mm had a worse prognosis during follow-up. The study on chronic thromboembolic pulmonary hypertension patients revealed that the S waves in V5, R waves in V1 + S waves in V5, S waves in I, and the QRS axis were predictors of mPAP ≥ 30 mm Hg [7]. Change in mPAP was associated with a change in the amplitudes in the ECG after balloon pulmonary angioplasty (BPA) and improvement in an R in V1 + S in V5 predicts a lower functional class in a 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%